ANALISIS PENENTUAN PRIORITAS PENGENDALIAN LOGISTIK BENCANA DI SULAWESI TENGAH - APRIAWAN, MOH. (Fakultas Ekonomi Universitas Tadulako, 2016)
This research aims to identify factors that affect disaster logistics control in Central Sulawesi and factors that become priority in disaster logistics control in Sulawesi Tengah. The respondents of this research are officials in Disaster Management Agency and Social Services Department of Central Sulawesi. This research uses the Analytical Hierarchy Process (AHP) method to portray the factors that affect the disaster logistics handling in Sulawesi Tengah in more detail. Data collection is done with in-depth interview and questionnaires distributed to the four samples. Sampling technique is purposive sampling or judgmental sampling. The data is processed using the Microsoft Office Excel 2007. Based on the analysis, it is shown that: there are five factors that affect disaster logistics handling in Central Sulawesi; (1) human resource, (2) uncertainty, (3) collaboration and cooperation,(4) facility, and (5) funding. Human resource is the priority factor in disaster logistics handling in Central Sulawesi with 0.6 point, whereas training is the main factor that affects the quality of human resource with 0.8 point.